Minorias linguisticas aborigenes en Chile - Valencia, Alba (Revista Chilena de Humanidades, 2016)
Professor Alba Valencia makes a synthesis of ethnolinguistic studies in Chile, supported by a solid and up-to-date bibliography. Her anide contributes to the scientific diffusion of this subject, which also acknowledges ethnolinguistic research at different centers of study in Chile.